Ion Trap Collisional Activation of c and z(•) Ions Formed via Gas-Phase Ion/Ion Electron Transfer Dissociation - Han, Hongling (2007)
A series of c- and z(•)-type product ions formed via gas-phase electron transfer ion/ion reactions between protonated polypeptides with azobenzene radical anions are subjected to ion trap collision activation in a linear ion trap. Fragment ions including a-, b-, y-type and ammonia-loss ions are typically observed in collision induced dissociation (CID) of c ions, showing almost identical CID patterns as those of the C-terminal amidated peptides consisting of the same sequences. Collisional activation of z(•) species mainly gives rise to side-chain losses and peptide backbone cleavages resulting in a-, b-, c-, x-, y-and z-type ions. Most of the fragmentation pathways of z(•) species upon ion trap CID can be accounted for by radical driven processes. The side-chain losses from z(•) species are different from the small losses observed from the charge-reduced peptide molecular species in electron transfer dissociation (ETD), which indicates rearrangement of the radical species. Characteristic side-chain losses are observed for several amino acid residues, which are useful to predict their presence in peptide/protein ions. Furthermore, the unique side-chain losses from leucine and isoleucine residues allow facile distinction of these two isomeric residues.